Pre-exposure to hyperoxic air does not enhance power output during subsequent sprint cycling - Sperlich, B.; Schiffer, T.; Achtzehn, S.; Mester, J.; Holmberg, H. C. (European Journal of Applied Physiology, 2010)
Previous studies have indicated that aerobic pathways contribute to 13-27% of the energy consumed during short-term (10-20 s) sprinting exercise. Accordingly, the present investigation was designed to test the hypothesis that prior breathing of oxygen-enriched air (FinO2 = 60%) would enhance power output and reduce fatigue during subsequent sprint cycling. Ten well-trained male cyclists (mean ± SD age, 25 ± 3 years; height, 186.1 ± 6.9 cm; body mass, 79.1 ± 8.2 kg; maximal oxygen uptake [VO2max]: 63.2 ± 5.2 ml kg-1 min-1) took 25 breaths of either hyperoxic (HO) or normoxic (NO) air before performing 15 s of cycling at maximal exertion. During this performance, the maximal and mean power outputs were recorded. The concentration of lactate, pH, partial pressure of and saturation by oxygen, [H+] and base excess in arterial blood were assessed before and after the sprint. The maximal (1,053 ± 141 for HO vs. 1,052 ± 165 W for NO; P = 0.77) and mean power outputs (873 ± 123 vs. 876± 147 W; P = 0.68) did not differ between the two conditions. The partial pressure of oxygen was approximately 2.3-fold higher after inhaling HO in comparison to NO, while lactate concentration, pH, [H+] and base excess (best P = 0.32) after sprinting were not influenced by exposure to HO. These findings demonstrate that the peak and mean power outputs of athletes performing short-term intense exercise cannot be improved by pre-exposure to oxygen-enriched air.